2016
DOI: 10.1038/srep29489
|View full text |Cite
|
Sign up to set email alerts
|

4-aminopyridine reverses ataxia and cerebellar firing deficiency in a mouse model of spinocerebellar ataxia type 6

Abstract: Spinocerebellar ataxia type 6 (SCA6) is a devastating midlife-onset autosomal dominant motor control disease with no known treatment. Using a hyper-expanded polyglutamine (84Q) knock-in mouse, we found that cerebellar Purkinje cell firing precision was degraded in heterozygous (SCA684Q/+) mice at 19 months when motor deficits are observed. Similar alterations in firing precision and motor control were observed at disease onset at 7 months in homozygous (SCA684Q/84Q) mice, as well as a reduction in firing rate.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
127
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 92 publications
(135 citation statements)
references
References 38 publications
4
127
2
Order By: Relevance
“…In mouse models of SCA1, SCA2, and SCA6, ataxias which all display prominent Purkinje neuron involvement, potassium channel dysfunction is present 1, 2, 19. Since pyramidal signs are a feature of many SCAs, and some patients with SCA6 can exhibit downbeat nystagmus, patients seen through the University of Michigan Ataxia Clinic with either pyramidal signs or downbeat nystagmus were offered a trial of baclofen and chlorzoxazone.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In mouse models of SCA1, SCA2, and SCA6, ataxias which all display prominent Purkinje neuron involvement, potassium channel dysfunction is present 1, 2, 19. Since pyramidal signs are a feature of many SCAs, and some patients with SCA6 can exhibit downbeat nystagmus, patients seen through the University of Michigan Ataxia Clinic with either pyramidal signs or downbeat nystagmus were offered a trial of baclofen and chlorzoxazone.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have focused on restoring somatic spiking as an approach to improve motor function in mouse models of ataxia 2, 19, 20, 49. In this study, we illustrate that improving Purkinje neuron spiking indeed improves motor performance in the short‐term, an effect which has been previously illustrated using K Ca activators in a mouse model of SCA2 20.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found, however, that developmental torpedo density was normal in P11 SCA6 84Q/84Q mice compared to WT, suggesting that they are not directly related to later pathophysiology (P11 WT: 2.71 ± 0.90 torpedoes/section; P11 SCA6 84Q/84Q : 2.61 ± 0.54 torpedoes/section; not significantly different, P = 0.92; Figure 8B , left). We also measured the density of Purkinje cell torpedoes in SCA6 84Q/84Q and litter-matched mice at 7 months, when cerebellar-related motor deficits are observed without detectable Purkinje cell loss (Jayabal et al, 2015, 2016a), and found that torpedo density was low at 7 months and similar in both WT and SCA6 84Q/84Q mice (7 month WT: 0.57 ± 0.20 torpedoes/section; 7 month SCA6 84Q/84Q : 0.42 ± 0.13 torpedoes/section; not significantly different; P = 0.53; Figure 8B , middle). Note that we observe higher torpedo numbers in P11 mice than 7-month-old mice in both WT and SCA6 84Q/84Q mice, which is consistent with our observations of a transient developmental peak of torpedoes at P11 ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…We recently found that 4‐AP improves motor function and firing deficits in a mouse model of SCA6 (Jayabal et al . ); taken together with its effects on SCA1 (Hourez et al . ), this suggests that common treatments for multiple SCAs may be possible.…”
mentioning
confidence: 99%